Cs-137 AND Co-60 CONCENTRATION REMOVAL ON RADIOACTIVE LIQUID WASTE BY ION EXCHANGE AND COAGULATION-FLOCCULATION METHOD - Pinky Septria Adella; Asih Wijayanti; Dwi Indrawati; Sugeng Purnomo (Universitas Trisakti, 2017)
Radioactive liquid waste is a hazardous and toxic waste which comes from nuclear research laboratory. This waste may cause explosion when treated with evaporator. Aim: This research was intended to reduce and determine the best removal method of Cs-137 and Co-60 from radioactive liquid waste. Methodology and Result: Methods used in this research are ion exchange and coagulation-flocculation method. In ion exchange method used two types of reactor that is continuous reactor and batch reactor with variables of debit, material type, mesh size and mass of material, while in coagulation-flocculation method used jar test with ferro sulfate coagulant dose variables. Continuous reactor consisting of separating funnel and chromatography column with a diameter of 4 cm and height 60 cm, whereas in batch reactor used jar test stirrer. The application of radioactive liquid waste treatment is done using selected method, with the start condition for Cs-137 of 3 x 10-5 mCi/L and for Co-60 of 4.8 x 10-6 mCi/L. Application of Ion Exchanger with Continuous Reactor Speed 60 mL/10 sec and Coagulation-Flocculation with dose of 100 mmol/L in pH 8 effluent result the value for Cs-137 and Co-60 that undetected or very little, below 10-6 mCi/L. Conclusion, significance and impact study: The conclusion of this study is suitable with the Government Regulation Number 10 of 1997 about nuclear power, the limit of quality standard for Cs-137 and Co-60 is below 10-6 mCi/L. So the appropriate method to treat of Cs-137 and Co-60 are Ion Exchanger with Continuous Reactor Speed 60 mL/10 sec and Coagulation-Flocculation with dose of 100 mmol/L in pH 8.